2017
DOI: 10.3174/ajnr.a5152
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Grading System for Skull Base Chordoma

Abstract: BACKGROUND AND PURPOSE: Skull base chordoma has been widely studied in recent years, however, imaging characteristics of this tumor have not been well elaborated. The purpose of this study was to establish an MR imaging grading system for skull base chordoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…MR imaging is important not only for diagnosing and differentiating disease but also in predicting prognosis. 3,16,24 Among the 32 patients who did not undergo adjuvant radiation therapy in the present series, R EN and tumor blood supply were demonstrated as independent factors for PFS. Tian et al 16 and Lin et al 17 have also had similar results, which suggested that R EN was a risk factor for PFS.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…MR imaging is important not only for diagnosing and differentiating disease but also in predicting prognosis. 3,16,24 Among the 32 patients who did not undergo adjuvant radiation therapy in the present series, R EN and tumor blood supply were demonstrated as independent factors for PFS. Tian et al 16 and Lin et al 17 have also had similar results, which suggested that R EN was a risk factor for PFS.…”
Section: Discussionmentioning
confidence: 56%
“…14,15 Recent studies have suggested that MR imaging signal intensity ratios on different sequences (ratio of tumor-to-pons signal intensity on T1 FLAIR [R T1 ]; ratio of tumor-to-pons signal intensity on T2 [R T2 ]; ratio of tumor-to-pons signal intensity on enhanced T1 FLAIR [R EN ]) are useful in predicting outcomes. Tian et al 16 revealed that higher R T2 predicted diminished tumor progression and higher R EN predicted more rapid tumor progression; this correlation between R EN and recurrence or progression was also shown by Lin et al 17 However, neither of these studies showed evidence for the possible explanation of signal intensity difference.…”
mentioning
confidence: 81%
“…[37][38][39][40] However, prior radiology literature addressing skull base chordomas has focused largely on identifying diagnostic imaging features, with only 1 recent study investigating the use of imaging as a prognostic tool. 36 In this study, we present findings suggesting that enhancement characteristics of skull base chordomas may be predictive of the clinical course.…”
mentioning
confidence: 71%
“…[33][34][35] While some studies have posited a correlation between MR imaging characteristics and histologic grade, analyses with larger samples have failed to demonstrate a statistically significant correlation between imaging features and chordoma histology. 33,34,36 Aside from its standard use as a diagnostic tool, MR imaging has demonstrated prognostic utility for many entities, with extensive literature supporting the use of signal intensity measurements in predicting prognosis for a variety of tumors. [37][38][39][40] However, prior radiology literature addressing skull base chordomas has focused largely on identifying diagnostic imaging features, with only 1 recent study investigating the use of imaging as a prognostic tool.…”
mentioning
confidence: 99%
“…Recurrent patients have undergone previous combined treatments such as surgery and RT and both factors may explain why ceramides are significantly different in the two groups [25,31,32,33]. Since the recurrent tumor type and previous treatments represented a significant negative prognostic factor relating to worse OS and PFS in previous studies, a raising in ceramides content in SBCs could act as a negative prognostic factor [16,34,35,36]. We showed that there is also a concomitant rise in both ceramides and dihydroceramides and such a finding could be related to an activation of the de-novo pathway, but further analyses are needed.…”
Section: Discussionmentioning
confidence: 99%